2015
DOI: 10.1044/2015_aja-14-0030
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Group Audiological Rehabilitation for Unaided Adults With Hearing Impairment and Their Significant Others

Abstract: Working adults with hearing impairment who do not use amplification can benefit from GAR sessions. Significant others of working adults with hearing impairment experience third-party disability, which can also be alleviated through participation in GAR sessions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 42 publications
1
9
0
3
Order By: Relevance
“…These applications of eHealth are in-keeping with the large body of qualitative research that describes the wide-ranging psychosocial impacts of hearing impairment, and in particular, the negative emotions experienced by both the person with hearing impairment and their significant others as a result of communication difficulties (Heffernan et al 2016; Jonsson & Hedelin 2018; Lucas et al 2018; Punch et al 2019). This finding also aligns with the growing emphasis on patient- and family-centered hearing care and the perceived benefits associated with involving significant others in the hearing rehabilitation process (Preminger 2003; Habanec & Kelly-Campbell 2015; Meyer et al 2015). Current hearing services are typically device focused and as such, audiologists do not always discuss alternative interventions such as communication education (Grenness et al 2015b; Convery et al 2018); however, the findings here show that adults with hearing impairment and their significant others would value the use of ICTs to provide further education about communication.…”
Section: Discussionsupporting
confidence: 74%
“…These applications of eHealth are in-keeping with the large body of qualitative research that describes the wide-ranging psychosocial impacts of hearing impairment, and in particular, the negative emotions experienced by both the person with hearing impairment and their significant others as a result of communication difficulties (Heffernan et al 2016; Jonsson & Hedelin 2018; Lucas et al 2018; Punch et al 2019). This finding also aligns with the growing emphasis on patient- and family-centered hearing care and the perceived benefits associated with involving significant others in the hearing rehabilitation process (Preminger 2003; Habanec & Kelly-Campbell 2015; Meyer et al 2015). Current hearing services are typically device focused and as such, audiologists do not always discuss alternative interventions such as communication education (Grenness et al 2015b; Convery et al 2018); however, the findings here show that adults with hearing impairment and their significant others would value the use of ICTs to provide further education about communication.…”
Section: Discussionsupporting
confidence: 74%
“…35 Our data are consistent with previous research on the positive contributions of social support and incorporating consideration of communication partners into audiologic interventions. [47][48][49][50] Recognition of the severity of hearing loss accompanied by the availability of an actual resource for hearing loss seems to be an important step toward help-seeking and subsequent increased confidence and adjustment to disability, or self-efficacy. The pilot study outcomes are promising on the issue of access to care and reducing disparities in demonstrating that, out of this sample, a majority of clients reported improvements in communication and well-being as well as accessing the hearing health care system through primary care, specialty care, and self-management.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study fit within the literature showing beneficial effects of group aural rehabilitation programs. [47][48][49][50][51][52] As characteristic of group intervention formats, participants identified the collaborative environment and opportunities to learn from peers with hearing loss as important components of the program. Gaining social support from their communication partners and other group members also contributed positively toward building participants' efficacy in managing hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in the present research, it can be administered within the clinic with the help of the clinician, or can be used at home, either alone or with a family member. Indeed, input from family members is strongly encouraged; research has shown family-centred care improves communication within families and reduces third-party disability [ 43 , 44 ]. Family inclusion can provide a comprehensive overview of family communication difficulties [ 45 ], and increases the likelihood of strong family member support if their needs are heard and met.…”
Section: Discussionmentioning
confidence: 99%